Studi Tentang Komunikasi Bahasa Menurut Jahidz Dan Ibnu Jinni - Azzah Diana Mardhotillah; Afiyatul Maulidiyah; Aulia Rohmah; Muflihah (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2025)
The study of language communication according to Jahiz and Ibnu Jinni provides deep insight into classical linguistic thought in the Arabic context.